2022
DOI: 10.1002/jmri.28110
|View full text |Cite
|
Sign up to set email alerts
|

Can Bone Erosion in Axial Spondyloarthropathy be Detected by Ultrashort Echo Time Imaging? A Comparison With Computed Tomography in the Sacroiliac Joint

Abstract: Background Structural lesion evaluation in axial spondyloarthropathy (SpA) can improve accuracy of diagnosis. However, structural lesions (bone erosions) are difficult to be assessed using conventional MRI compared to computed tomography (CT). Purpose To evaluate the diagnostic performance of ultrashort echo time (UTE) for detecting bone erosion in axial SpA compared to T1WI and three‐dimensional double‐echo steady‐state (3D DESS) imaging using CT as the reference standard. Study Type Retrospective. Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This provides outstanding contrast between the articular cartilage and the bone cortex interface. Hahn et al found that 2D-UTE imaging provided better diagnostic performance for identifying SIJ bone erosion than did T1-weighted imaging and 3D DESS sequences ( 19 ). In our study, fewer erosions were detected with the 3D-UTE sequence than with CT.…”
Section: Discussionmentioning
confidence: 99%
“…This provides outstanding contrast between the articular cartilage and the bone cortex interface. Hahn et al found that 2D-UTE imaging provided better diagnostic performance for identifying SIJ bone erosion than did T1-weighted imaging and 3D DESS sequences ( 19 ). In our study, fewer erosions were detected with the 3D-UTE sequence than with CT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several MRI sequences sensitive to cortical structures that may allow accurate cortical and trabecular bone assessment have been recently reported [52 ▪▪ ,53,54–56]. These pulse sequences, including 3D MRI such as zero echo time (ZTE) and ultrashort echo time (USTE) as well as black bone (BB) sequences, add an average of 4–5 min to the total MRI examination time and were shown to be more accurate as well as more specific and sensitive than T1-w sequences for the detection of erosions, sclerosis, and joint space changes [52 ▪▪ ,57 ▪▪ ] while at the same time performing similar to CT in the assessment of bony structures of the SIJs (Fig. 4) [58 ▪ ].…”
Section: Mri Of the Sacroiliac Joints: A Potential One-stop Shop For ...mentioning
confidence: 99%